O papel do ator-Xamã na instauração-cênica-ritual - Silva, José Nilton dos Santos (2019)
The research proposed by this dissertation is centered in the sense of understanding my role as a possible shaman-actor from a scenic-ritual instauration entitled "Y". The creative process put into practice and analyzed was inspired by the occult studies of Kabala, Hermetic Philosophy and Tarot. The theoretical thinking that guided this work is based on the works of Antonin Artaud, being a reference matrix for this investigation. The creative process has taken into account the concept of Scenic Insertion elaborated by Nara Salles (2004) that incorporates elements of the visual arts into the field of theater and performance and proposes residues to be left at the place of installation and as a creative procedure explores the memory and corporeal-vocal matrices of the scene settlers. My proposal for a work by the actor / actress as a shaman starts from the ideas presented and discussed by Antonin Artaud in his work, The Theater in its Double (1985) proposing this look to be added to the concept of Scenic Insertion being added to it. From this reference and from the scenic-dramaturgical elements developed in the scenic setting "Y" I describe the possibilities of relations between the mystical work of an actor / actress and a shaman, realizing how I appropriate the mystical stimuli used in creating a new procedure for the theater understood as ritual. The essay writing appears as a series of letters, these being directed to the Actor and director Antonin Artaud. The text sessions were ordered and structured based on the Rider's Kabbalistic Tarot (2009), so for each letter addressed to Artaud a tarot image was offered as an initial stimulus for the development of the theme.